Mastering lambdas Java programming in a multicore world - Naftalin, Maurice 1951- (McGraw-Hill Education, 2015)
This book describes how the lambda-related features of Java SE 8 will enable Java to meet the challenges of next-generation parallel hardware architectures. It explains how to write lambdas, and how to use them in streams and in collection processing, providing code examples throughout. Readers will learn how to use lambda expressions to take full advantage of performance improvements provided by today's multicore hardware. Topics include: why lambdas were needed, and how they will change Java programming; syntax of lambda expressions; basic operation of streams and pipelines; using collectors and reduction to end pipelines; creating streams; spliterators, the fork/join framework, and exceptions; examining stream performance with microbenchmarking; and API evolution using default methods. --